2018
DOI: 10.1111/maec.12517
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the bacterial communities of sponges inhabiting the remote western Indian Ocean island of Mayotte

Abstract: Marine sponges are known to host diverse and abundant communities of microbial symbionts. It has been generally assumed that the bacterial communities of low microbial abundance (LMA) sponges are less diverse than those of high microbial abundance (HMA) sponges. In this study, we used next‐generation sequencing technology to explore the bacterial communities of several biotopes including sponges, seawater, and sediment from the remote Western Indian Ocean island of Mayotte. The species investigated were the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 63 publications
(93 reference statements)
6
18
0
Order By: Relevance
“…Indeed, sponges belonging to the genera Scopalina (order Scopalinida) have been characterized as LMA sponges, which are generally assumed to have a less diverse bacterial communities (low phylum-level diversity) than high microbial abundance (HMA) sponges [ 64 , 65 ]. Nonetheless, our result is in agreement with the study by de Voogd et al (2018), which reported that some LMA sponges from Mayotte harbored a more diverse bacterial community at the phylum level than HMA sponges (e.g., Stylissa carteri , order Scopalinida: 29) [ 66 ]. Our result supports their conclusion that a true dichotomy between HMA and LMA sponges does not appear to exist [ 66 ].…”
Section: Resultssupporting
confidence: 93%
“…Indeed, sponges belonging to the genera Scopalina (order Scopalinida) have been characterized as LMA sponges, which are generally assumed to have a less diverse bacterial communities (low phylum-level diversity) than high microbial abundance (HMA) sponges [ 64 , 65 ]. Nonetheless, our result is in agreement with the study by de Voogd et al (2018), which reported that some LMA sponges from Mayotte harbored a more diverse bacterial community at the phylum level than HMA sponges (e.g., Stylissa carteri , order Scopalinida: 29) [ 66 ]. Our result supports their conclusion that a true dichotomy between HMA and LMA sponges does not appear to exist [ 66 ].…”
Section: Resultssupporting
confidence: 93%
“…The Paratetilla sp. microbial community composition reported here is similar to what has been reported for Paratetilla in other biogeographic regions, with the dominance of Proteobacteria (Alpha-and Gammaproteobacteria), Chloroflexi, and Actinobacterial taxa (Thomas et al, 2016;De Voogd et al, 2018;Cleary et al, 2019). The Cinachyrella sp.…”
Section: Species Specificity Of Tetillid Sponge Prokaryotic Microbialsupporting
confidence: 87%
“…In earlier papers, we described the morphological features and habitat preferences of H. erectus, J. splendens, L. paradoxa, P. cf. spiculifer and S. carteri Cleary et al,2015Cleary et al, , 2018de Voogd et al 2019). We were unable to identify the sponge Svenzea novo sp.…”
Section: Samplingmentioning
confidence: 89%
“…In previous studies, we assigned HMA or LMA status to the species H. erectus, J. splendens, S. carteri and L. paradoxa based on compositional traits of their prokaryotic communities. Hyrtios erectus was consistently classified as an HMA species (Cleary et al, 2015(Cleary et al, , 2018de Voogd et al 2015de Voogd et al , 2019 in line with Lurgi et al (2019). Likewise, P. cf.…”
mentioning
confidence: 82%
See 1 more Smart Citation